Cannabis knowledge and implications for health: Considerations regarding the legalization of non-medical cannabis. (October 2020) - Zamengo, Luca; Frison, Giampietro; Zwitser, Guus; Salomone, Alberto; Freeman, Tom P
Cannabis contains over a hundred of different cannabinoids, of which Δ 9 -tetrahydrocannabinol (THC) and cannabidiol (CBD) are the most well studied. The use of high-potency cannabis, containing high concentrations of THC and low concentrations of CBD, has been linked to adverse health outcomes, particularly for adolescents and young adults. Recently, an increase in cannabis potency has been observed in jurisdictions that legalized the sale of cannabis for non-medical purposes. Moreover, an increase of cannabis use and cannabis-related emergency treatment have also been observed in these jurisdictions. At the same time, risk perception regarding cannabis use has decreased in these populations. Trivializing language and an increased appearance of commercial cannabis in the public space may lead to a generalized underestimation of the risks of cannabis use. New regulation models principally focus on the creation of a legal cannabis market economy, the diversion of profits from illegal markets, and the reduction of costs associated with prohibition. However, an approach that specifically focuses on the rights to the health and safety of the individual should be considered in order to reduce the risks associated with cannabis legalization. Such an approach should promote and protect individual and social health and safety, establish a strict quality control of legal cannabis products regulated according to THC and CBD content, and eliminate all sorts of incentives to use, thus providing a more consistent, sustainable, and ethical framework for the legalization of non-medical cannabis use.